The Impact of Mild Stroke on Participation in Physical Fitness Activities - Mary Hildebrand; Megan Brewer; Timothy Wolf (Stroke Research and Treatment)
Objective. To compare participation in moderate to high intensity physical activities in persons before and after a mild stroke. Methods. We used data from the Cognitive Rehabilitation and Research Group to examine changes in moderate to high intensity physical activity participation in persons who had a mild stroke as defined by an NIH Stroke Scale score of less than 6 (N=127). Using the Activity Card Sort, we compared the participants' high-demand leisure activity (leisure activities that are moderate to high intensity physical activities) participation at 6-months after stroke with their prestroke level. Results. We found a significant decrease in numbers of high-demand leisure activities in all participants and in each demographic group after mild stroke. Conclusion. These results suggest that persons after mild stroke are not retaining the high-demand leisure activities they were doing prior to their stroke. Health professionals must promote participation in high-demand leisure activities in patients with mild stroke as a tool to enhance health and fitness.